The Electronic Green Initiatives Database on Campus (eGREENi) through spatial technology applications / Nur Huzeima Mohd Hussain ... [et al.] - Mohd Hussain, Nur Huzeima; Abdullah, Suzanah; Ahmad, Nur Azfahani (2022)
Prior to achieving sustainable campus recognition and strategizing green initiatives, a comprehensive and accessible green initiatives campus database is subsequently necessary. The relevant activities, programs and implementation of the green agenda need to be coordinated and documented. Therefore, in line with the university and sustainable development goal (SDG) desire in pursuing sustainable cities and communities, the green campus documentation needs to be digitalized. The Electronic Green Initiatives Database on Campus (e-GREENi) was created using a combination of Geographical Information System (GIS), and the use of Survey123 Mobile Apps technologies. This database focuses on the development of GIS and a web-based system to assist administrators in managing Green Initiative records more effectively. This database collection was also conducted to coordinate and map the location of Green Initiatives on campus. This system is well equipped with a search function that can provide information about the initiatives by using an Internet browser. In addition, the use of a quick response in e-GREENi database allows various types of information to be directly accessible and easily generated with fast-reading accuracy. Consequently, e-GREENi application would also be a profound basis for the new Green Innovation application besides coordinating several Green Initiatives case studies namely The Green Roof, Solar Charging Hub, 3R initiatives, fertigation, Musang King Valley, and Kelulut Farm around UiTM Perak Branch, Seri Iskandar Campus.